Disseminated emm Type 12 Group A Streptococcus and Review of Invasive Disease. (November 2015) - Heeke, Arielle L.; Blumberg, Henry M.; Perry, Jason M.; Weiss, David S.; Crispell, Emily K.; Satola, Sarah W.; Salinas, Jorge L.
Abstract : Abstract: The authors present a case of invasive group A Streptococcus (GAS) in a previously healthy 63-year-old male complicated by trans-esophageal echocardiogram negative endocarditis, septic arthritis, and multiple cerebral septic emboli. Despite antibiotics and drainage of his largest brain abscess, the patient expired. This case highlights the potential mortality from invasive GAS disease. Included is a review of current literature regarding invasive GAS that addresses its presentation, prevalence, virulence and treatment. Abstract : Supplemental Digital Content is Available in the Text.